Surgical management in severe laryngomalacia - Raja Lope Ahmad, Raja Ahmad Al'konee (2005)
Majority of infants with laryngomalacia does not requires any surgical intervention because the disorder is self-limited. However in the severe cases which associated with failure to thrive, repeated cyanosis, obstructive apnea and / or cor pulmonale, surgical intervention are required. Traditionally in severe cases have been treated with tracheotomy. In the last decade, several literatures reported successful ablation of the redundant supraglottic tissue with either microscissors or carbon dioxide laser. Here we reported our early experience with 4 infants who were diagnosed with severe laryngomalacia and were treated with laser aryepiglottoplasty. The aim of this presentation is to highlighted the surgical technique and the effectiveness of bilateral aryepiglottoplasty in the treatment of an infant with severe laryngomalacia. All 4 patients had resolution of the symptoms and there were no complications noted.